2021
DOI: 10.1002/bbb.2293
|View full text |Cite
|
Sign up to set email alerts
|

Cattle manure management using microbial fuel cells for green energy generation

Abstract: The increased use of estrogens in modern livestock farming has caused them to enter the environment and they have become a serious human health concern. Studies have suggested that animal waste treatment using bio-electrochemical systems may reduce their environmental impact. Bioelectrochemical systems hold great potential as green bioenergy conversion systems utilizing different biowastes as the feedstock. The present work involves the development of a laboratory-scale microbial fuel cell (MFC) for energy gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…They observed that the optimal COD and BOD levels were reduced by an average of 80% in both the cattle manures. The power output can also be increased by 22 times if 5 units are stacked in parallel (Syed et al 2021). All these studies have shown that the use of ultrasonication as a pre-treatment procedure on cathode material (activated carbon), substrate (rice mill water) for MFC and bovine manures yielded positive results in terms of energy generation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They observed that the optimal COD and BOD levels were reduced by an average of 80% in both the cattle manures. The power output can also be increased by 22 times if 5 units are stacked in parallel (Syed et al 2021). All these studies have shown that the use of ultrasonication as a pre-treatment procedure on cathode material (activated carbon), substrate (rice mill water) for MFC and bovine manures yielded positive results in terms of energy generation.…”
Section: Discussionmentioning
confidence: 99%
“…The process of cavitation develops more quickly at a low-frequency level of 20 kHz to 40 kHz (Zhang et al 2007;Hawrylik and Butarewicz 2021). The application of low-frequency ultrasound has a broad range of applications in the field of biotechnology and environmental remediation (Foladori et al 2007;Hawrylik and Butarewicz 2021) including pre-treatment of electrode materials for improved electron transfer (Koo and Jung 2021), substrate modification (Raychaudhuri and Behera 2020) and microbial pre-treatment which all aimed towards better power generation in an MFC setup (Syed et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…[13] reported buffalo dung as a low‐cost substrate containing large amounts of carbohydrates, an optimal C/N ratio and a rich microbial flora belonging to Firmicutes , Clostridia , Bacteroidetes and Proteobacteria . The presence of electrogens such as Purple photosynthetic bacteria in buffalo dung makes it a preferable substrate and a biocatalyst for higher power generation in MFC and also suitable as a biofertilizer promoting the plant growth [13]. The rich microbial flora and high C/N ratio may be the reasons for better power output.…”
Section: Resultsmentioning
confidence: 99%
“…Buffalo manure has been used in this study as the source of microbial flora for the PMFC operation. Syed et al [13] reported buffalo dung as a lowcost substrate containing large amounts of carbohydrates, an optimal C/N ratio and a rich microbial flora belonging to Firmicutes, Clostridia, Bacteroidetes and Proteobacteria.…”
Section: Electricity Generationmentioning
confidence: 99%
See 1 more Smart Citation